2010
DOI: 10.1111/j.1365-2672.2010.04876.x
|View full text |Cite
|
Sign up to set email alerts
|

Kill rate of mastitis pathogens by a combination of cefalexin and kanamycin

Abstract: Aim:  To assess the bacterial killing rate produced by a combination of cefalexin and kanamycin at two different concentration ratios. Methods and Results:  Time–kill kinetics of cefalexin and kanamycin, individually and in combination, were determined against one strain each of Escherichia coli, Staphylococcus aureus, Streptococcus agalactiae, Streptococcus dysgalactiae and Streptococcus uberis. The combination was tested using two fixed ratios (cefalexin : kanamycin ratios of 1·25 : 1 and 1 : 2·3) and two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…This combination offers an extended spectrum of activity compared with that of each individual drug. The 2 antimicrobials have been shown to demonstrate synergy against major mastitis pathogens such as Staphylococcus aureus, Streptococcus uberis, and Escherichia coli, offering potential for increased efficacy compared with using either of the antibiotics alone (Ganiere and Denuault, 2009;Maneke et al, 2011). Combination therapy can also be useful in situations in which resistance of a particular target pathogen to one agent has emerged but susceptibility to the other agent persists (Pillar et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This combination offers an extended spectrum of activity compared with that of each individual drug. The 2 antimicrobials have been shown to demonstrate synergy against major mastitis pathogens such as Staphylococcus aureus, Streptococcus uberis, and Escherichia coli, offering potential for increased efficacy compared with using either of the antibiotics alone (Ganiere and Denuault, 2009;Maneke et al, 2011). Combination therapy can also be useful in situations in which resistance of a particular target pathogen to one agent has emerged but susceptibility to the other agent persists (Pillar et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the effect of cefquinome was time-dependent, but that the kill rate and drug concentration had no obvious correlation. Maneke et al ( 31 ) compared the kill rate of cefalexin and kanamycin alone or combination against five mastitis pathogens. The results show that the higher concentrations can produce faster kill for most strains.…”
Section: Discussionmentioning
confidence: 99%
“…When assessing combination treatment, it may be valuable to determine the rate-of-kill of the PLOS NEGLECTED TROPICAL DISEASES combination as well as individual partner drugs, as some combinations may achieve a faster rate-of-kill than any of the partners individually (e.g. [29]). Such combinations would offer the potential of shorter treatment regimens.…”
Section: Discussionmentioning
confidence: 99%